FLUID INCLUSION CHARACTERISTICS OF AURIFEROUS ARINEM AND BANTARHUNI QUARTZ VEINS, ARINEM, WEST JAVA, INDONESIA - Euis Tintin Yuningsih (Jurnal Geologi dan Sumberdaya Mineral, 2010)
A microthermometric study of fluid inclusions were carried out on the samples from the epithermal gold-silver-base metal mineralization of Arinem and Bantarhuni veins of Arinem deposit from different levels, stages and minerals types (quartz, sphalerite and calcite) to understand the characteristics of the fluid inclusions trapped, and to determine the physical and chemical environments of ore mineral deposition. The results of primary fluid inclusions measurement of stages I and II of main ore mineralization revealed that Arinem and Bantarhuni quartz veins are in the average range of 194.0º–267.3ºC, and sphalerite samples are 194.1º–241.2ºC. The measurement indicates a general decrease of temperature with decreasing depth and an increasing paragenetic time. The evidence of boiling was measured from substage IA of the Arinem vein with the filling temperatures of these inclusions range from 216.8º–247.3ºC. Under such condition, with an average fluid density of 0.861 g/cm3 and a pressure of about 21.7 bars, the paleo-depth would have about 235 meters. Fluid inclusions assemblages from main stages I and II from all levels commonly show a narrow range in Tm values (0.18–4.43 wt.% NaClequiv.). This is also marked in fluid inclusions assemblages from late stage (stage III) of barren quartz (0.35–3.87 wt.% NaClequiv.). Raman spectroscopic analyses of CO2, N2, H2S and CH4 on selected fluid inclusions of the Arinem vein samples, shows no volatile components other than H2O.Keywords: Arinem, Bantarhuni, fluid inclusion, microthermometry, quartz, salinity.